(untitled) (Papeles, 2014)
The article proposes the formal computational scaffolds that guide online consultation in order to develop metacognitive skills in finding information design. Some studies on information seeking conclude that students do not respond adequately to their learning tasks when they consult the Web, then simply copy and paste the contents consulted, so that the quality of the work is not as expected. The studies attribute this to the lack of metacognitive skills that prevents students to search plan, monitor the strategies implemented and evaluate the selected information. In this regard, we propose a Metacognitive Scaffolding for the search of information (Ambi), which is designed based on input from a model of self-regulated learning based on the theory of information processing occurs.